Publisher Correction: Synthesis method of asymmetric gold particles. Issue 1 (December 2017) - Jun, Bong-Hyun; Murata, Michael; Hahm, Eunil; Lee, Luke
A correction to this article has been published and is linked from the HTML version of this paper. The error has not been fixed in the paper.